The System of Student Selction in Chilean Universities - Donoso, Sebastián; Hawes, Gustavo (Education Policy Analysis Archives, 2000)
Chile has a peculiar centralised system for the selection of students to undergraduate programs; this is the case for the more traditional universities associated in the Council of Rectors. This process has been in operation for over thirty years, and its major instruments and procedures, as well as its foundations, are still in force. The contents of the different tests are currently under review; however, the system will continue to be the same in the future. Changes come from the new conditions created by the 1981 reform of the Chilean higher education system. Important modifications were introduced in the constitution, organization and financing of universities. The university system was suddenly opened; from the original eight universities, the system expanded to sixty-five. New conditions and social, professional and technical demands are having an impact on the higher education system as a whole and, specifically, on the student selection processes. This article includes a description of the process of academic selection for entrance into the Chilean university system. Next we analyze the Test of Academic Performance (PAA), the main instrument of this selection. Finally the PAA is analyzed and criticized from two points of view: its psychometric relevance and its implicit model of intelligence.